Magnetic field amplification by shocks in galaxy clusters: application to radio relics - Iapichino, Luigi; Brüggen, Marcus (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. Merger shocks induce turbulence in the intracluster medium (ICM), and, under some circumstances, accelerate electrons to relativistic velocities to f